2006
DOI: 10.1111/j.1574-6968.2006.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane topology of the chromate transporter ChrA ofPseudomonas aeruginosa

Abstract: The membrane topology of the plasmid-encoded Pseudomonas aeruginosa ChrA protein, which effluxes chromate ions, was determined by the analysis of translational fusions with reporter enzymes alkaline phosphatase and beta-galactosidase. A novel 13-TMS (transmembrane segments) topology, with the N-terminus located in the cytoplasm and the C-terminus in the periplasmic space, was consistent with the enzyme activities determined in both Escherichia coli and P. aeruginosa. Alignment of the two halves of ChrA showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…(Desai et al, 2008), Serratia marcescens (Mondaca et al, 2002), Vogococcus fluvialis (Mistry et al, 2010), Arthrobacter aurescens (Horton et al, 2006), Burkholderia cepacia (Wani et al, 2007), Microbacterium sp. (Pattanapipitpaisal et al, 2001) Beveridge, 2001;Jimenez-Mejia et al, 2006;Rahman et al, 2007) and Pseudomonas ambigua (McLean and Beveridge, 2001). Recently, Ilias et al (2011) reported the reduction of Cr (VI) to Cr (III) in the presence of Staphylococcus aureus and Pediococcus pentosaceus isolated from tannery effluents.…”
Section: Introductionmentioning
confidence: 91%
“…(Desai et al, 2008), Serratia marcescens (Mondaca et al, 2002), Vogococcus fluvialis (Mistry et al, 2010), Arthrobacter aurescens (Horton et al, 2006), Burkholderia cepacia (Wani et al, 2007), Microbacterium sp. (Pattanapipitpaisal et al, 2001) Beveridge, 2001;Jimenez-Mejia et al, 2006;Rahman et al, 2007) and Pseudomonas ambigua (McLean and Beveridge, 2001). Recently, Ilias et al (2011) reported the reduction of Cr (VI) to Cr (III) in the presence of Staphylococcus aureus and Pediococcus pentosaceus isolated from tannery effluents.…”
Section: Introductionmentioning
confidence: 91%
“…P. aeruginosa ChrA is a 416-aa protein that displays a topology of 13 TMSs (Jímenez-Mejía et al 2006). The ChrA transporter functions as a chemiosmotic pump that extrudes chromate from the cytoplasm using the proton-motive force (Alvarez et al 1999;Pimentel et al 2002) (Fig.…”
Section: Chromate Effluxmentioning
confidence: 98%
“…Bioreduction of toxic Cr(VI) to non-toxic Cr(III), through chromate reductase enzymes, has been demonstrated in several bacterial species including Pseudomonas sp. (Jimenez-Mejia et al 2006), Bacillus sp., Leucobacter sp. and Exiguobacterium sp.…”
Section: Introductionmentioning
confidence: 99%